Building Capacities in Open Knowledge: Recommendations for Library and Information Science Professionals and Schools - Santos-Hermosa, Gema; Atenas, Javiera (Frontiers in Education, 2022)
The impact openness to knowledge is having, not only in the Higher Education (HE) sector but at public and institutional policy level, is largely due to the efforts of information professionals and researchers, as thanks to these two groups, initiatives such as open access (OA), open education (OE) and open science (OS) have changed the way in which research is being taught, conducted, and communicated. Openness is a way to democratise access to knowledge developed through public funds, and this movement has been led by informational professionals worldwide, however, we have observed that to a large extent, professional development in areas different areas of openness is rather self-taught, informal, mentored or continuous, but not formalised in information science, documentation or scientific educational programmes. In this exploratory research, gathered evidence on how (or if) openness to knowledge is being taught by reviewing a series of syllabi from undergrad and postgraduate programmes in Library and Information Science schools (LIS) sampled from universities which either/ a) are leading the agenda in OA, OS or OE; b) have policies in OA, OS or OE; c) have national / federal mandates, policies, or regulations regarding OA, OS or OE and also a range of non-formal and/or lifelong learning training offer in these same three areas. We found that while LIS schools are not providing formal training to gain skills and competencies in Openness, their libraries are offering different kinds of training in this respect. On the other hand, the good intentions and Openness awareness of policies have not yet materialised in actions to ensure capacity building. Research implications are to be able to influence the development of capacity building in open knowledge, by providing solid evidence for enhancing curriculum advancement in LIS Schools and by proposing some recommendations in this direction.